Detecting triple systems with gravitational wave observations - Meiron, Y; Kocsis, B; Loeb, A (American Astronomical Society, 2017)
The Laser Interferometer Gravitational Wave Observatory (LIGO) has recently discovered gravitational waves (GWs) emitted by merging black hole binaries. We examine whether future GW detections may identify triple companions of merging binaries. Such a triple companion causes variations in the GW signal due to: (1) the varying path length along the line of sight during the orbit around the center of mass; (2) relativistic beaming, Doppler, and gravitational redshift; (3) the variation of the light-travel time in the gravitational field of the triple companion; and (4) secular variations of the orbital elements. We find that the prospects for detecting a triple companion are the highest for low-mass compact object binaries which spend the longest time in the LIGO frequency band. In particular, for merging neutron star binaries, LIGO may detect a white dwarf or M-dwarf perturber at a signal-to-noise ratio of 8, if it is within 0.4 R⊙ distance from the binary and the system is within a distance of 100 Mpc. Stellar mass (supermassive) black hole perturbers may be detected at a factor 5 × (103×) larger separations. Such pertubers in orbit around a merging binary emit GWs at frequencies above 1 mHz detectable by the Laser Interferometer Space Antenna in coincidence.